THE CLASSIFICATION OF HABERMAS EPISTEMOLOGY AND ITS IMPLICATION TOWARD SOCIAL-CULTURAL RESEARCH METHODOLOGY - Anas Saidi (Jurnal Masyarakat dan Budaya, 2015)
As a branch of philosophy which studies the nature of science, epistemology seems to be neglected in the research world. Some of young researchers assume that epistemology is only an abstract philosophical material unrelated with the methodology. As a consequence, research is often conducted based on the known methods rather than the nature of the reality. From the very beginning, therefore, the research has been biased in methodology. This paper discusses the classification of Habermas’ epistemology. Habermas has classified the science paradigm into three categories, namely (1) Positivism (Technical knowledge interest or dominative knowledge), (2) Interpretative Paradigm (Humanistic or practical knowledge Interest or descriptive science), and (3) Critical Paradigm (Emancipatory knowledge interest/ liberating knowledge). Understanding the strengths and weaknesses of each paradigm will encourage the researchers to determine the appropriate methodology based on the the nature of reality. Keywords: implication, epistemology, methodology, social-cultural, Jurgen Habermas